On optical solitons of the Schrodinger-Hirota equation with power law nonlinearity in optical fibers - Aslan, Ebru Cavlak; Tchier, Fairouz; İnç, Mustafa (Academic Press Ltd- Elsevier Science Ltd, 2017)
In this study, we acquire optical soliton solutions of the Schrodinger-Hirota equation (SHE) in optical fiber. The integration algorithm employed in this work is the Jacobi elliptic function (JEF). We acquire new type JEF solutions, bright and dark optical solitons that are valuable in the field of optoelectronics. Constraint conditions are presented for the obtained solitons. The results show that this method is a powerful and efficient mathematical tool for solving problems in optical fibers. The remarkable features of such solitons are demonstrated by several interesting figures. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Soliton; JEF; Optical soliton; SHE